Museum Julião Sarmento Collection. Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
Lisbon's new contemporary art centre, SILD, aims to house the private collection of one of the Portuguese artists with the greatest international projection ever – Julião Sarmento. The project to house this new institution was based on a pre-existing food warehouse (known as the Blue Pavilion), located on Avenida da Índia in the Belém area. This ware-house was acquired by the Lisbon City Council from the Companhia Industrial de Portugal e Colónias in 1942. Since then, it has been used for various storage and event organisation purposes and, since 2017, the project for its reconversion into a museum has been under development. The new building is expected to contain large exhibition spaces, as well as the necessary support spaces for the museum's operation – such as a multi-purpose room, reserve areas, offices and staff support areas. Since the area of the pre-existing building would not be able to accommodate the whole programme, it is necessary to introduce a basement, as well as to change its spatial organisation. This operation requires new structural solutions and new technical and safety infrastructures, while maintaining the elevations and the industrial resonance of some of its elements.